PENGARUH KOMUNIKASI INTERPERSONAL, KERJASAMA TIM, KEPEMIMPINAN TRANSFORMASIONAL DAN PENGAMBILAN KEPUTUSAN TERHADAP KINERJA PEGAWAI PADA PERWAKILAN BKKBN PROVINSI SULAWESI TENGGARA - Taufiq Ridi; Nasrul Nasrul; Sinarwaty Sinarwaty (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The aims of this research are: 1). To examine the effect of interpersonal communication on employee performance, 2) To examine the effect of teamwork on employee performance. 3). To examine the effect of transformational leadership on employee performance. 4). To examine the effect of decision making on employee performance. 5) To examine the effect of interpersonal communication, teamwork, transformational leadership, and decision making on employee performance.The research design used is quantitative research. The population in this study were all employees of the Representative Office of the National Population and Family Planning Agency of Southeast Sulawesi Province, using saturated sampling and obtained as many as 57 people. Data collection in the form of documentation and questionnaires. The data analysis technique uses multiple regression models with the help of SPSS 20 software.The results showed that 1). Interpersonal communication, Teamwork, Transformational Leadership, and Decision Making simultaneously have                        positive and significant effect on Employee Performance. 2). Interpersonal communication has positive and significant effect on employee performance. 3). Teamwork has positive and significant effect on employee performance. 4). Transformational leadership has positive and significant effect on employee performance. 5). Decision making has positive and significant effect on employee performance.